Serum trimethylamine N-oxide and its precursors are associated with the occurrence of mild cognition impairment as well as changes in neurocognitive status - Bai, He; Zhang, Yao; Tian, Peiying; Wu, Yani; Peng, Ruiheng; Liang, Bin; Ruan, Wenli; Cai, Enmao; Lu, Ying; Ma, Mingfeng; Zheng, Liqiang (Frontiers in Nutrition, 2024)
Background: This study aims to examine the association between gut microbe-dependent trimethylamine N-oxide (TMAO) and its precursors (choline, betaine, and carnitine) levels and mild cognition impairment (MCI), alongside changes in the Chinese version of the Montreal Cognitive Assessment-Basic (ΔMoCA-BC) score in rural adults.Methods: Drawing data from a large-scale epidemiological study conducted in rural areas of Fuxin County, Liaoning Province, China. 1,535 participants free from brain-related ailments were initially surveyed. MCI was assessed through the MoCA-BC score. Logistic regression models and restricted cubic spline were used to investigate the association between TMAO and its precursors levels and MCI. Additionally, the association between TMAO and its precursors levels and ΔMoCA-BC was analyzed using a generalized linear model in the longitudinal study.The average age of the study participants was 58.6 ± 9.4 years and the prevalence rate of MCI was 34.5%. With the second quartile as the reference in the logistic regression model, the OR for risk of MCI in the highest quartile for TMAO, betaine, and carnitine was 1.685 (95% CI: 1.232-2.303, P = 0.001), 2.367 (95% CI: 1.722-3.255, P < 0.001), and 2.239 (95% CI: 1.742-3.295, P < 0.001), respectively. The OR of choline for the highest versus lowest quartile was 2.711 (95% CI: 2.012-3.817, P < 0.001) for the risk of MCI. We find a J-shaped association between betaine (P non-linear = 0.001) and carnitine (P non-linear = 0.003) levels and MCI. Furthermore, TMAO and its precursors levels were associated with ΔMoCA-BC in the third and fourth quartiles group (All P < 0.05).The findings suggest the existence of an optimal concentration range for serum levels of TMAO, betaine, and carnitine that mitigates MCI risk, paving the way for enhanced dietary interventions aimed at preventing and treating MCI.